Waste recycling of cathode ray tube glass through industrial production of transparent ceramic frits - Karaahmet, Oguz; Cicek, Bugra (TAYLOR & FRANCIS INC, 2019)
Cathode ray tube (CRT) glass contains significant amounts of alkali and alkaline earth oxides, making it a useful by-product for use in the ceramics industry. Among the various alkali oxides present, those of strontium (SrO), calcium (CaO), and magnesium (MgO) are well known flux materials used widely in the ceramics industry. The most effective flux, SrO, is also a limited resource. In this study, we aimed to develop an environmentally friendly, low-cost method for recycling CRT waste by using it to produce transparent ceramic frits on an industrial scale. Four different samples were fabricated containing between 13 and 25 wt.% CRT panel glass. The color values, sintering behaviors, phases, and microstructural properties of the corresponding samples were analyzed and compared. The results indicate that a composition containing 25 wt.% CRT panel glass could pass the ISO 10545 test. Thus, the results confirm that CRT glass can be used to inexpensively produce transparent ceramic frits at an industrial scale. Implications: The recycling of electronic waste (e-waste), including CRT waste, has increased by high rates of computer and TV consumption. This increase in consumption is likely to increase the rate at which CRTs are discarded. However, CRTs cannot be recycled in the desired amount. Owing to the high silicate, barium and strontium content of CRTs, it has great potential for glass ceramics such as frits. CRT panel glass to produce commercial transparent frit at low cost through an industrial production route for use in single-fire sintered products. Thus, CRT wastes can be recycled cost-effective, sustainable and environmentally friendly.
Keywords: PARTICLE-SIZE DISTRIBUTION; PANEL GLASS; APPEARANCE; SURFACE; GLAZES; Engineering; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences